PENGARUH LINGKUNGAN KERJA, TEKANAN KERJA, DISIPLIN KERJA DAN TRANSFORMASI DIGITAL 5.0 TERHADAP KINERJA PEGAWAI UPTD BALAI LATIHAN KERJA KOTA BANDA ACEH - Presilawati, Febyolla; Maizi, Zahrul; Rizkye, Putroe Hemalyana (Jurnal Bisnis Digital, 2024)
The purpose of this study was to determine the Influence of Work Environment, Work Pressure, Work Discipline and Digital Transformation 5.0 on Employee Performance at the Banda Aceh City Job Training Center UPTD. The population in this study was 39 respondents. The research data was obtained through interviews and filling out questions/questionnaires. Hypothesis testing using multiple linear regression analysis, the results of the study using the correlation analysis of determination were intended to determine the effect of independent variables on dependent variables with a correlation coefficient value of 84.4%. The results of the study showed that the simultaneous test between the variables Work Environment, Work Pressure, Work Discipline and Digital Transformation 5.0 had an effect on Employee Performance which then partially namely Work Environment, Work Pressure, Work Discipline and Digital Transformation 5.0 had an effect on Employee Performance at the Banda Aceh City Job Training Center UPTD